Adaptation of Mangrove Ecotourism Management to Coastal Environment Changes in the Special Region of Yogyakarta - KHAKHIM, Nurul; MUSTHOFA, Azis; WICAKSONO, Arief; LAZUARDI, Wahyu; PRATAMA, Dimas Novandias Damar; MARFAI, Muh Aris (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).14, 2021)
Ecotourism is a practice of utilizing natural ecosystems to support education and conservation efforts. In the Special Region of Yogyakarta (SRY), Indonesia, two mangrove ecosystems have been designated as protected areas and ecotourism sites. However, it is undeniable that the need for space for infrastructure development has been detrimental to these areas. This research set out to identify changes occurring nearby mangrove ecosystems and the impacts they would potentially have in the future. It used a triangulation method that combined secondary data analysis, observation, and primary data collection through in-depth interviews. The observed coastal environments experienced, among others, extensive conversion of agricultural land for the Yogyakarta International Airport (YIA) construction, increased tourism growth and pressures, and varying artificial modifications in parts of mangrove ecosystems utilized for mass tourism; all of which could disrupt sustainability and reduce the ecological functions of mangroves. Intensive aquaculture and iron sand mining in the vicinity could also negatively affect the mangrove ecosystem and ecotourism. Within a certain period, these anthropogenic activities are most likely to pose significant threats to the preservation of mangrove ecotourism. Regional spatial plans are an example of instruments required to regulate sustainable spatial planning and protect mangrove ecosystems.